Mechanical Properties of 3D Printed Concrete and its Application in Civil Engineering - Liu, Ming (Transactions on Engineering and Technology Research, 2024)
Rapid urbanization worldwide is placing higher demands on the efficiency and quality of the construction industry. Three-dimensional Printed Concrete (3DPC) technology, with its digital design and additive manufacturing processes, offers a promising avenue for advancement. This paper discusses the potential and challenges of 3DPC in terms of mechanical properties, environmental impact and economic benefits. The technological process of 3DPC, its advantages over traditional concrete, and its optimization in key mechanical properties are studied. The environmental benefits of Three-dimensional (3D) printing technology, including reduced construction waste, material savings and lower energy consumption, are also analysed. In addition, the economic advantages of 3D printing technology are described, including labour costs, material costs and construction efficiency. The conclusion emphasizes that 3DPC technology has substantial advantages in improving construction efficiency and realizing complex design. Case studies such as Qingpu Park in Shanghai and the Museum of the Future in Dubai have further demonstrated the practicality and innovative potential of 3DPC technology. The research of 3DPC technology has important theoretical and practical significance for promoting technological innovation and realizing sustainable development in the construction industry.